Determination of Forces on Anchor Blocks and Stability Analysis in a 3 Dimensional Plane with Vector Approach - Atreya, Gaurav; Shakya, Narendra Man (Nepal Journal of Civil Engineering, 2021)
The Anchor blocks are the structures that take most of the forces acting on the pipe bends and transfer it safely to the ground. Since the stability of the Anchor Blocks is a function of its weight, the economic design comes with accurate calculation of the forces. Although several sources have the design calculations for Anchor Blocks, there is room for improvements for 3D calculations. The calculation of the forces is hard to visualize in a two-dimensional plane as numerous planes have to be made for the analysis. The purpose of this paper is to use the 3D vector mechanics so that forces can all be represented by global vectors in X, Y & Z direction and henceforth are easy to study. By doing so the intermittent calculations, as well as the end results, are efficient, coherent and scalable (to any number of a joint like T-joint, or combination of bends and joints). The formulae and procedures are developed with consideration of developing a well-organized CAD-based software for an even better analysis of a variety of irregular shapes in the future with reduced human efforts.